Environment-friendly tough barrier film and preparation method thereof
By using SiO2 hollow sphere template to prepare PGA/PBAT Janus nanosheets during the blending process of PGA and PBAT, the problem of poor blend compatibility is solved, the capacity-enhancing efficiency and barrier performance are significantly improved, and the application scope is expanded.
Patent Information
- Application Number
- CN202411991543.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the prior art, PGA and PBAT have poor compatibility during blending, which affects the quality and application range of its final product. Traditional compatibilizers have problems such as large amount of addition, low efficiency and lack of functionality.
PGA/PBAT Janus nanosheets were prepared by performing in-situ melting reaction using SiO2 hollow spheres as templates and added to the matrix PBAT/PGA to improve the capacity-enhancing efficiency of the blend.
It effectively improves the capacity-enhancing efficiency of the blend, enhances the mechanical properties and barrier properties of the blend, and broadens its application areas.
Smart Images

Figure CN119775729A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional materials, and in particular to an environmentally friendly strong and tough barrier film and a preparation method thereof. Background Art
[0002] At present, a single polymer cannot meet the requirements of mechanical properties, functionality, etc. in industrial applications. The common method to improve the performance of a single polymer is blending modification. Polybutylene adipate / terephthalate (PBAT) is a thermoplastic biodegradable plastic, which is copolymerized by adipic acid, butanediol and terephthalic acid. It has the characteristics of PBA and PBT, and has good ductility, elongation at break, etc. Polyglycolic acid (PGA) is a high-performance aliphatic polyester material with excellent gas barrier properties, high mechanical strength and biodegradability. Blending PGA with PBAT is expected to further improve the strength, modulus and barrier properties of both, and further improve the performance and application areas of PBAT materials. However, there is a problem of poor compatibility between the two during the blending process, which affects the quality and application range of the final product. Therefore, the universal strategy to improve compatibility is to add a compatibilizer. However, traditional compatibilizers have problems such as large addition amount, low efficiency and lack of functionality. Summary of the invention
[0003] In view of the above problems existing in the prior art, the present invention provides an environmentally friendly tough barrier film and a preparation method thereof. The present invention uses SiO2 hollow spheres as templates and performs in-situ melting reaction to prepare PGA / PBAT Janus nanosheets, which are added to the matrix PBAT / PGA to better disperse at the interface between the two phases, thereby effectively improving the volume expansion efficiency of the blend.
[0004] The technical solution of the present invention is as follows:
[0005] The first object of the present invention is to provide a PGA / PBAT Janus nanosheet, which uses SiO2 hollow spheres as templates and polyglycolic acid and poly(adipate / butylene terephthalate) are respectively modified on both sides of the template.
[0006] A second object of the present invention is to provide a method for preparing PGA / PBAT Janus nanosheets, comprising the following steps:
[0007] (1) PGA is mixed with 4,4'-methylenebis(phenyl isocyanate) (MDI), curcumin and SiO2 hollow spheres. After the reaction is completed, unreacted PGA is washed away with hexafluoroisopropanol to obtain SiO2 hollow spheres with PGA grafted on the outer surface;
[0008] (2) The SiO2 hollow spheres with PGA grafted on the outer surface are ultrasonically crushed to obtain SiO2-PGA nanosheets, which are then reacted with glycidyl methacrylate (GMA) and PBAT to obtain the PGA / PBAT Janus nanosheets.
[0009] In one embodiment of the present invention, in step (1), the molar ratio of PGA to MDI is 1:2-4; the mass ratio of curcumin to PGA is 1:15-25.
[0010] In one embodiment of the present invention, in step (1), the particle size of the SiO2 hollow spheres is 2.5-3.5 μm; and the mass ratio of the SiO2 hollow spheres to PGA is 1:30-50.
[0011] In one embodiment of the present invention, in step (1), the blending temperature is 220-240° C., the blending time is 5-6 min, and the rotation speed is 80-100 rpm.
[0012] In one embodiment of the present invention, in step (1), the specific process is: fully dried PGA, MDI, curcumin and SiO2 hollow spheres are melt blended at 220-240°C for 5-6 minutes at a rotation speed of 80-100 rpm. Then, the blended product is fully dissolved in hexafluoroisopropanol, free PGA is washed away, and finally SiO2 hollow spheres grafted with PGA are obtained by centrifugal washing.
[0013] In one embodiment of the present invention, in step (2), the ultrasonic disruption conditions are: 500-550W ultrasonic treatment for 1-1.5h.
[0014] In one embodiment of the present invention, in step (2), the mass ratio of SiO2-PGA nanosheets, PBAT and GMA is 1:30-50:15-25.
[0015] In one embodiment of the present invention, in step (2), the blending temperature is 140-160° C., the blending time is 7-9 min, and the blending speed is 50-60 rpm.
[0016] In one embodiment of the present invention, in step (2), the specific process is:
[0017] The SiO2 hollow spheres with PGA grafted on the outer surface were dispersed in anhydrous ethanol and subjected to ultrasonic treatment at 500-550W for 1-1.5h to break the hollow spheres into pieces to obtain SiO2-PGA nanosheets; thereafter, they were melt-blended with glycidyl methacrylate (GMA) and PBAT at 140-160°C for 7-9min; then, they were washed with chloroform and centrifuged to remove free PBAT to obtain PGA / PBAT Janus nanosheets.
[0018] The third object of the present invention is to provide an environmentally friendly tough barrier film, comprising the following raw materials in parts by weight: 60-90 parts of polybutylene adipate / terephthalate (PBAT), 10-40 parts of polyglycolic acid (PGA), and 0.5-5 parts of PGA / PBAT Janus nanosheets;
[0019] PGA / PBAT Janus nanosheets use SiO2 hollow spheres as templates, and polyglycolic acid (PGA) and poly(butylene adipate / terephthalate) (PBAT) are modified on both sides of the templates, respectively.
[0020] A fourth object of the present invention is to provide a method for preparing the above-mentioned environmentally friendly tough barrier film, comprising the following steps:
[0021] 60-90 parts of poly(butylene adipate / terephthalate), 10-40 parts of poly(glycolic acid) and 0.5-5 parts of PGA / PBATJanus nanosheets are melt-blended and then formed to obtain a PBAT / PGA blend film, namely the environmentally friendly tough barrier film.
[0022] In one embodiment of the present invention, the specific steps of the method for preparing an environmentally friendly tough barrier film are:
[0023] 60-90 parts of poly(butylene adipate / terephthalate), 10-40 parts of poly(glycolic acid) and 0.5-5 parts of PGA / PBAT Janus nanosheets are blended at 220-240°C for 5-6 minutes, and then extruded to form a film or sheet, and then rapidly cooled to below 20°C to make its crystallinity less than 15%; then the cooled film or sheet is biaxially stretched at 50-55°C by a flat film biaxial stretching process, and then heat treated at 55-75°C to obtain the environmentally friendly tough barrier film;
[0024] or,
[0025] 60-90 parts of poly(butylene adipate / terephthalate), 10-40 parts of poly(glycolic acid) and 0.5-5 parts of PGA / PBAT Janus nanosheets are blended at 220-240°C for 7-9 minutes, and then formed into a tube embryo through a tube die. The tube embryo is quickly cooled to below 20°C to make its crystallinity less than 15%. The cooled tube embryo is then inflated, stretched and shaped at 50-55°C using a tube film biaxial stretching process to obtain the environmentally friendly strong barrier film.
[0026] A fifth object of the present invention is to provide an application of the above-mentioned environmentally friendly tough barrier film for use in the fields of textiles, fire protection, packaging bags or agricultural films.
[0027] The beneficial technical effects of the present invention are:
[0028] The PGA / PBAT Janus nanosheets prepared by the melt in-situ reaction of the present invention have higher grafting efficiency, more stable covalent bonds, and excellent volume expansion effect. The grafted curcumin during the blending process gives the blend film good UV resistance and ammonia response properties, thereby broadening its application range.
[0029] Through the biaxial stretching of flat films or tubular films, the mechanical properties of the blend film are significantly improved. In addition, due to the effect of the stretching force field, the orientation of PGA / PBAT Janus nanosheets in the blend and the crystallization of PGA synergistically improve the barrier properties of the blend film, which is beneficial to its application in packaging, ground film and other fields, and effectively broadens the application field of the blend. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Atomic force microscope images of nanosheets at different stages in Example 1;
[0031] Among them, (a) SiO2 nanosheets after ultrasonic crushing of ungrafted SiO2 (3μm) hollow spheres; (b) SiO2-PGA nanosheets; (c) PGA / PBAT Janus nanosheets. DETAILED DESCRIPTION
[0032] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0033] Embodiment 1:
[0034] A method for preparing PGA / PBAT Janus nanosheets comprises the following steps:
[0035] (1) Weighing 50 g of fully dried PGA, 12.5 g of MDI, 3 g of curcumin, and 0.6 g of SiO2 hollow spheres with a particle size of 2.5 μm, and premixing them in a torque rheometer mixing chamber for 5 min, with the mixing temperature and rotation speed being 220° C. and 80 rpm, respectively, to obtain a PGA / SiO2 blend; then washing with deionized water and hexafluoroisopropanol, and centrifugally drying, to obtain SiO2 hollow spheres with PGA grafted on the outer surface;
[0036] (2) The SiO2 hollow spheres grafted with PGA on the outer surface were dispersed in anhydrous ethanol and ultrasonically treated (500W) for 1 h to break them into pieces, thereby obtaining SiO2-PGA nanosheets;
[0037] (3) Weigh 30 g of fully dried PBAT, 15 g of GMA and 1 g of SiO2-PGA nanosheets and place them in the mixing chamber of a torque rheometer for premixing for 7 min. The mixing temperature and speed are 140 °C and 50 rpm, respectively, to obtain a PBAT / SiO2-PGA blend; then wash with chloroform and centrifuge to remove free PBAT to obtain the final Janus nanosheets.
[0038] Depend on Figure 1 It can be seen that the surface roughness of the nanosheet increased from 0.3nm to 2.5nm, indicating that the surface was grafted with PGA and PBAT molecular chains, proving the successful synthesis of PGA / PBAT Janus nanosheets. At the same time, the thickness of the nanosheet also increased from 5.1nm to 6.4nm, further proving the success of the synthesis.
[0039] Embodiment 2:
[0040] A method for preparing PGA / PBAT Janus nanosheets comprises the following steps:
[0041] (1) Weigh 50 g of fully dried PGA, 25 g of MDI, 2 g of curcumin and 1 g of SiO2 hollow spheres with a particle size of 3.5 μm and place them in the mixing chamber of a torque rheometer for premixing for 6 min at a mixing temperature of 240°C and a rotation speed of 100 rpm to obtain a PGA / SiO2 blend; then wash with deionized water and hexafluoroisopropanol and centrifuge and dry to obtain SiO2 hollow spheres with PGA grafted on the outer surface.
[0042] (2) The SiO2 hollow spheres grafted with PGA on the outer surface were dispersed in anhydrous ethanol and subjected to ultrasonic treatment (550W) for 1.5 h to break them into pieces, thereby obtaining SiO2-PGA nanosheets;
[0043] (3) Weigh 50 g of fully dried PBAT, 25 g of GMA and 1 g of SiO2-PGA nanosheets and place them in the mixing chamber of a torque rheometer for premixing for 9 min. The mixing temperature and speed are 160 °C and 60 rpm, respectively, to obtain a PBAT / SiO2-PGA blend; then wash with chloroform and centrifuge to remove free PBAT to obtain the final Janus nanosheets.
[0044] Embodiment 3:
[0045] A method for preparing PGA / PBAT Janus nanosheets comprises the following steps:
[0046] (1) Weigh 50 g of fully dried PGA, 12.5 g of MDI, 3 g of curcumin, and 1 g of SiO2 hollow spheres with a particle size of 3 μm and place them in a torque rheometer mixing chamber for premixing for 8 min at a mixing temperature of 235°C and a rotation speed of 50 rpm to obtain a PGA / SiO2 blend; then wash with deionized water and hexafluoroisopropanol and centrifuge and dry to obtain SiO2 hollow spheres with PGA grafted on the outer surface.
[0047] (2) The SiO2 hollow spheres grafted with PGA on the outer surface were dispersed in anhydrous ethanol and ultrasonically treated (550W) for 1 h to break them into pieces, thereby obtaining SiO2-PGA nanosheets;
[0048] (3) Weigh 25 g of fully dried PBAT, 15 g of GMA and 1 g of SiO2-PGA nanosheets and place them in the mixing chamber of a torque rheometer for premixing for 8 min. The mixing temperature and speed are 150 °C and 50 rpm, respectively, to obtain a PBAT / SiO2-PGA blend; then wash with chloroform and centrifuge to remove free PBAT to obtain the final Janus nanosheets.
[0049] Embodiment 4:
[0050] A method for preparing PGA / PBAT Janus nanosheets comprises the following steps:
[0051] (1) Weigh 25 g of fully dried PGA, 12.5 g of MDI, 1 g of curcumin and 1 g of SiO2 hollow spheres with a particle size of 3 μm and place them in the mixing chamber of a torque rheometer for premixing for 8 min at a mixing temperature of 235°C and a rotation speed of 50 rpm to obtain a PGA / SiO2 blend; then wash with deionized water and hexafluoroisopropanol and centrifuge and dry to obtain SiO2 hollow spheres with PGA grafted on the outer surface.
[0052] (2) The SiO2 hollow spheres grafted with PGA on the outer surface were dispersed in anhydrous ethanol and ultrasonically treated (550W) for 1 h to break them into pieces, thereby obtaining SiO2-PGA nanosheets;
[0053] (3) Weigh 25 g of fully dried PBAT, 15 g of GMA and 1 g of SiO2-PGA nanosheets and place them in the mixing chamber of a torque rheometer for premixing for 8 min. The mixing temperature and speed are 150 °C and 50 rpm, respectively, to obtain a PBAT / SiO2-PGA blend; then wash with chloroform and centrifuge to remove free PBAT to obtain the final Janus nanosheets.
[0054] Application Example 1
[0055] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0056] 70 parts of PBAT, 30 parts of PGA, and 0.5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 235°C, the screw speed was 200rpm, and the extrusion was 5 minutes. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to 20°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film, wherein the stretching temperature was 50°C, the heat treatment temperature was 60°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0057] Application Example 2
[0058] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0059] 60 parts of PBAT, 40 parts of PGA, and 0.5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 220°C, the screw speed was 200rpm, and the extrusion was 5 minutes. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to 20°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film, wherein the stretching temperature was 50°C, the heat treatment temperature was 55°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0060] Application Example 3
[0061] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0062] 90 parts of PBAT, 10 parts of PGA, and 5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 240°C, the screw speed was 200rpm, and the extrusion was 6 minutes. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to 20°C. The cooled thin sheet was biaxially stretched by a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film, wherein the stretching temperature was 55°C, the heat treatment temperature was 75°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0063] Application Example 4
[0064] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0065] 70 parts of PBAT, 30 parts of PGA, and 0.5 parts of PGA / PBAT Janus nanosheets prepared in Example 2 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 235°C, the screw speed was 200rpm, and the extrusion was 5 minutes. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to 20°C. The cooled thin sheet was biaxially stretched by a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film, wherein the stretching temperature was 50°C, the heat treatment temperature was 60°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0066] Application Example 5
[0067] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0068] 70 parts of PBAT, 30 parts of PGA, and 0.5 parts of PGA / PBAT Janus nanosheets prepared in Example 3 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 235°C, the screw speed was 200rpm, and the extrusion was 5 minutes. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to 20°C. The cooled thin sheet was biaxially stretched by a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film, wherein the stretching temperature was 50°C, the heat treatment temperature was 60°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0069] Application Example 6
[0070] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0071] 70 parts of PBAT, 30 parts of PGA, and 0.5 parts of PGA / PBAT Janus nanosheets prepared in Example 4 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 235°C, the screw speed was 200rpm, and the extrusion was 5 minutes. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to 20°C. The cooled thin sheet was biaxially stretched by a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film, wherein the stretching temperature was 50°C, the heat treatment temperature was 60°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0072] Application Example 7
[0073] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0074] 70 parts of PBAT, 30 parts of PGA, and 1.5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 235°C, the screw speed was 200rpm, and the extrusion was 5 minutes. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to 20°C. The cooled thin sheet was biaxially stretched by a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film, wherein the stretching temperature was 50°C, the heat treatment temperature was 60°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0075] Application Example 8
[0076] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0077] 70 parts of PBAT, 30 parts of PGA, and 3 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 235°C, the screw speed was 200rpm, and the extrusion was 5 minutes. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to 20°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film, wherein the stretching temperature was 50°C, the heat treatment temperature was 60°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0078] Application Example 9
[0079] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0080] 70 parts of PBAT, 30 parts of PGA, and 5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 235°C, the screw speed was 200rpm, and the extrusion was 5 minutes. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to 20°C. The cooled thin sheet was biaxially stretched by a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film, wherein the stretching temperature was 50°C, the heat treatment temperature was 60°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0081] Application Example 10
[0082] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0083] 70 parts of PBAT, 30 parts of PGA, and 0.5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 235°C, the screw speed was 150rpm, and the extrusion was 7 minutes. After granulation, the pellets were dried in a vacuum oven. The film was prepared by casting using a casting machine and the film was quickly cooled by cooling water. The screw temperature was 240°C and the screw speed was 200rpm. The above-mentioned tube embryo was inflated and stretched at 50°C at the same time by a tube film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film. The heat treatment temperature was 60°C, the blowing ratio was 3 times, and the stretching ratio was 5 times.
[0084] Application Example 11
[0085] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0086] 60 parts of PBAT, 40 parts of PGA, and 0.5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 220°C, the screw speed was 150rpm, and the extrusion was 7 minutes. After granulation, the pellets were dried in a vacuum oven. The film was prepared by casting using a casting machine and the film was quickly cooled by cooling water. The screw temperature was 240°C and the screw speed was 200rpm. The above-mentioned tube embryo was inflated and stretched at 50°C at the same time by a tube film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film. The heat treatment temperature was 55°C, the blowing ratio was 3 times, and the stretching ratio was 5 times.
[0087] Application Example 12
[0088] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0089] 90 parts of PBAT, 10 parts of PGA, and 0.5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 240°C, the screw speed was 150rpm, and the extrusion was 9 minutes. After granulation, the pellets were dried in a vacuum oven. The film was prepared by casting using a casting machine and the film was quickly cooled by cooling water. The screw temperature was 240°C and the screw speed was 200rpm. The above-mentioned tube embryo was inflated and stretched at 55°C at the same time by a tube film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film. The heat treatment temperature was 75°C, the blowing ratio was 3 times, and the stretching ratio was 5 times.
[0090] Application Example 13
[0091] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0092] 70 parts of PBAT, 30 parts of PGA, and 1.5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 235°C, the screw speed was 150rpm, and the extrusion was 7 minutes. After granulation, the pellets were dried in a vacuum oven. The film was prepared by casting using a casting machine and the film was quickly cooled by cooling water. The screw temperature was 240°C and the screw speed was 200rpm. The above-mentioned tube embryo was inflated and stretched at 50°C at the same time by a tube film biaxial stretching process, and then heat treated and cooled to room temperature to obtain an environmentally friendly tough barrier film. The heat treatment temperature was 60°C, the blowing ratio was 3 times, and the stretching ratio was 5 times.
[0093] Application Example 14
[0094] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0095] 70 parts of PBAT, 30 parts of PGA, and 3 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 235°C, the screw speed was 150rpm, and the extrusion was 7 minutes. After granulation, the pellets were dried in a vacuum oven. The film was prepared by casting using a casting machine and the film was quickly cooled by cooling water. The screw temperature was 240°C and the screw speed was 200rpm. The above-mentioned tube embryo was inflated and stretched at 50°C at the same time by a tube film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film. The heat treatment temperature was 60°C, the blowing ratio was 3 times, and the stretching ratio was 5 times.
[0096] Application Example 15
[0097] A method for preparing an environmentally friendly tough barrier film comprises the following steps:
[0098] 70 parts of PBAT, 30 parts of PGA, and 5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 235°C, the screw speed was 150rpm, and the extrusion was 7 minutes. After granulation, the pellets were dried in a vacuum oven. The film was prepared by casting using a casting machine and the film was quickly cooled by cooling water. The screw temperature was 240°C and the screw speed was 200rpm. The above-mentioned tube embryo was inflated and stretched at 50°C at the same time by a tube film biaxial stretching process, and then heat treated and cooled to room temperature to obtain the environmentally friendly tough barrier film. The heat treatment temperature was 60°C, the blowing ratio was 3 times, and the stretching ratio was 5 times.
[0099] Comparative Example 1
[0100] Compared with Application Example 1, no Janus nanosheets were added, and other conditions remained unchanged, as follows:
[0101] 70 parts of PBAT and 30 parts of PGA were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 235°C and a screw speed of 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to 20°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a barrier film, wherein the stretching temperature was 50°C, the heat treatment temperature was 60°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0102] Comparative Example 2
[0103] Compared with Application Example 1, the number of PGA / PBAT Janus nanosheets added is changed to 8, and other conditions remain unchanged, as follows:
[0104] 70 parts of PBAT, 30 parts of PGA, and 8 parts of Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 235°C and a screw speed of 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to 20°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a barrier film, wherein the stretching temperature was 50°C, the heat treatment temperature was 60°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0105] Comparative Example 3
[0106] Compared with Application Example 1, the number of PBAT and PGA is changed to 50, and other conditions remain unchanged, as follows:
[0107] 50 parts of PBAT, 50 parts of PGA, and 0.5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 235°C and a screw speed of 200rpm. The dried pellets were extruded into thin sheets by a screw extruder and quickly cooled to 20°C. The cooled thin sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a barrier film, wherein the stretching temperature was 50°C, the heat treatment temperature was 60°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0108] Comparative Example 4
[0109] Compared with Application Example 1, the flat film is not biaxially stretched, and other conditions remain unchanged, as follows:
[0110] 70 parts of PBAT, 30 parts of PGA, and 0.5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried, stirred in a high-speed mixer for 2 minutes, and put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 235° C. and a screw speed of 200 rpm. The dried pellets were extruded into sheets by a screw extruder and quickly cooled to 20° C. to obtain a barrier film.
[0111] Comparative Example 5
[0112] Compared with Application Example 10, Janus nanosheets are not added, and other conditions remain unchanged, as follows:
[0113] 70 parts of PBAT and 30 parts of PGA were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation. The screw temperature was 235°C and the screw speed was 150rpm. After granulation, the pellets were dried in a vacuum oven. The film was prepared by casting using a casting machine and the film was quickly cooled by cooling water. The screw temperature was 240°C and the screw speed was 200rpm. The above-mentioned tube embryo was inflated and stretched at 50°C by a tube film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a barrier film. The heat treatment temperature was 60°C, the blowing ratio was 3 times, and the stretching ratio was 5 times.
[0114] Comparative Example 6
[0115] Compared with Application Example 10, the biaxial stretching of the tubular film is not performed, and other conditions remain unchanged, as follows:
[0116] 70 parts of PBAT, 30 parts of PGA, and 0.5 parts of PGA / PBAT Janus nanosheets prepared in Example 1 were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 235°C and a screw speed of 150rpm. After granulation, the pellets were dried in a vacuum oven. A film was prepared by casting using a casting machine and the film was quickly cooled by cooling water, with a screw temperature of 240°C and a screw speed of 200rpm to obtain a barrier film.
[0117] Comparative Example 7
[0118] Compared with Application Example 1, PBAT, PGA, curcumin, and SiO2 hollow microspheres (pure nanoparticles without any modification or grafting) are added together, and other conditions remain unchanged, as follows:
[0119] 70 parts of PBAT, 30 parts of PGA, 3 parts of curcumin, and 0.5 parts of SiO2 hollow microspheres were fully dried and stirred in a high-speed mixer for 2 minutes, and then put into an extruder for continuous melt extrusion and granulation, with a screw temperature of 235°C and a screw speed of 200rpm. The dried pellets were extruded into sheets by a screw extruder and quickly cooled to 20°C. The cooled sheets were biaxially stretched using a flat film biaxial stretching process, and then heat treated and cooled to room temperature to obtain a barrier film, wherein the stretching temperature was 50°C, the heat treatment temperature was 60°C, the transverse stretching ratio was 3 times, and the longitudinal stretching ratio was 3 times.
[0120] After being fully dried, the films obtained in the above application examples and comparative examples were tested for tensile properties at room temperature according to the GB / T 1040-2006 standard method. The tensile rate was set to 10 mm / min. At least 5 specimens were tested for the same sample and the average value was taken. The test results are shown in Table 1. The oxygen permeability of the material was tested using an oxygen permeability tester according to the GB / T 1038 standard method. The test conditions were 20°C, relative humidity 40%, sample thickness 20 μm, and film test area 38.48 cm 2 ; The water vapor transmission rate tester was used to test the moisture permeability of the material according to the GB / T 1037 standard method. The test conditions were 38°C, relative humidity 95%, sample thickness 20μm, and film test area 33cm 2 ; The crystallinity was measured by DSC with a heating rate of 10°C / min. The test results are shown in Table 2.
[0121] Table 1
[0122]
[0123]
[0124] Table 2
[0125]
[0126]
[0127] It can be seen from Table 1 and Table 2 that the breaking strength and elongation at break of polyglycolic acid, polyadipate / butylene terephthalate (Comparative Example 1) after adding Janus nanosheets (Application Example 1) are significantly improved compared to direct blending. It is shown that Janus nanosheets are evenly dispersed at the interface of the two phases at this time, and a good volume expansion effect is played, so the mechanical properties of the blends such as breaking strength and elongation at break are all improved. It can be seen from the PBAT / PGA blend films with different Janus nanosheet addition contents (Application Examples 6-9, 12-15) that with the addition of Janus nanosheets, compatibility is significantly improved, and the mechanical properties of the blends are also significantly improved. But when the content of Janus nanosheets is too much (Comparative Example 2), the compatibility and mechanical properties of the PBAT / PGA blend films have a certain decline, and the reason is that the distribution of nanosheets is uneven at this time, and too many nanosheets are agglomerated, which affects the mechanical properties of the blends. In addition, the proportion of the components of the blend also has a certain influence on the compatibility of the material (Comparative Example 3). When the mass ratio of PBAT and PGA is 1:1, the interface formed by the blend is larger and the volume expansion efficiency is lower, so the tensile strength and elongation at break of the material are not significantly improved. On the other hand, the present invention adopts a biaxial stretching process to make the barrier performance of the PBAT / PGA blend film (Application Examples 1-15) much higher than that of the blend film without biaxial stretching (Comparative Examples 4, 6). Under the action of the tensile force field. The Janus nanosheets are oriented in the blend, acting as a barrier and significantly improving the barrier performance. At the same time. The tensile force field promotes the crystallization performance of PGA, and synergizes with the Janus nanosheets to improve the barrier performance of the blend film. Compared with the blend film of simple blending (Comparative Example 7), the in-situ melting reaction used makes the grafting efficiency of the Janus nanosheets higher, the curcumin is more evenly dispersed, and the performance is best (Application Examples 1-15). In conclusion, the present invention prepares an environmentally friendly strong barrier film, which is simple and practical, easy to industrialize and can be used in the fields of film packaging materials, agricultural greenhouse film materials, etc.
[0128] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. An environmentally friendly tough barrier film, characterized in that: The method comprises the following raw materials in parts by weight: 60-90 parts of poly(adipate / butylene terephthalate), 10-40 parts of poly(glycolic acid), and 0.5-5 parts of PGA / PBAT Janus nanosheets; PGA / PBAT Janus nanosheets use SiO2 hollow spheres as templates, and polyglycolic acid and poly(adipate / butylene terephthalate) are modified on both sides of the templates, respectively.
2. The environmentally friendly tough barrier film according to claim 1, characterized in that: The preparation method of Janus nanosheets is as follows: (1) PGA is mixed with 4,4'-methylenebis(phenyl isocyanate), curcumin and SiO2 hollow spheres. After the reaction is completed, unreacted PGA is washed away with hexafluoroisopropanol to obtain SiO2 hollow spheres with PGA grafted on the outer surface; (2) The SiO2 hollow spheres with PGA grafted on the outer surface are ultrasonically crushed to obtain SiO2-PGA nanosheets, which are then reacted with glycidyl methacrylate and PBAT to obtain the Janus nanosheets.
3. The environmentally friendly tough barrier film according to claim 2, characterized in that: In step (1), the molar ratio of PGA to MDI is 1:2-4; the mass ratio of curcumin to PGA is 1:15-25.
4. The environmentally friendly tough barrier film according to claim 2, characterized in that: In step (1), the particle size of the SiO2 hollow spheres is 2.5-3.5 μm; and the mass ratio of the SiO2 hollow spheres to PGA is 1:30-50.
5. The environmentally friendly tough barrier film according to claim 2, characterized in that: In step (1), the blending temperature is 220-240° C., the blending time is 5-6 min, and the rotation speed is 80-100 rpm.
6. The environmentally friendly tough barrier film according to claim 2, characterized in that: In step (2), the conditions for ultrasonic crushing are: 500-550W ultrasonic treatment for 1-1.5h; blending temperature is 140-160°C, blending time is 7-9min, and blending speed is 50-60rpm.
7. The environmentally friendly tough barrier film according to claim 2, characterized in that: In step (2), the mass ratio of SiO2-PGA nanosheets, PBAT and GMA is 1:30-50:15-25.
8. A method for preparing the environmentally friendly tough barrier film according to claim 1, characterized in that: The steps include: 60-90 parts of poly(butylene adipate / terephthalate), 10-40 parts of poly(glycolic acid) and 0.5-5 parts of PGA / PBATJanus nanosheets are melt-blended and then formed to obtain a PBAT / PGA blend film, namely the environmentally friendly tough barrier film.
9. The preparation method according to claim 8, characterized in that: The specific steps are: 60-90 parts of poly(butylene adipate / terephthalate), 10-40 parts of poly(glycolic acid) and 0.5-5 parts of PGA / PBAT Janus nanosheets are blended at 220-240°C for 5-6 minutes, and then extruded to form a film or sheet, and then rapidly cooled to below 20°C to make its crystallinity less than 15%; then the cooled film or sheet is biaxially stretched at 50-55°C by a flat film biaxial stretching process, and then heat treated at 55-75°C to obtain the environmentally friendly tough barrier film; or, 60-90 parts of poly(butylene adipate / terephthalate), 10-40 parts of poly(glycolic acid) and 0.5-5 parts of PGA / PBAT Janus nanosheets are blended at 220-240°C for 7-9 minutes, and then formed into a tube embryo through a tube die. The tube embryo is quickly cooled to below 20°C to make its crystallinity less than 15%. The cooled tube embryo is then inflated, stretched and shaped at 50-55°C using a tube film biaxial stretching process, and then heat treated at 55-75°C to obtain the environmentally friendly strong barrier film.
10. An application of the environmentally friendly tough barrier film according to claim 1, characterized in that: Used in textile, fire protection, packaging bags or agricultural film fields.
Citation Information
Patent Citations
Method for preparing self-repairing hydrogel by using modified Janus nanosheets
CN110684209A
Fully biodegradable food preservative film and preparation method thereof
CN115124744A
Degradable multi-layer high-barrier film as well as preparation method and application thereof
CN116512721A
Janus nanoparticle, preparation method thereof and bio-based polyester composition prepared from Janus nanoparticle
CN118812863A
Amphiphilic nanosheets and methods of making the same
US20170173546A1